Energy yield from the two-layered Bosphorus exchange flow by marine current turbines: Challenges and implications - Altas, Furkan; Orhan, Kadir; Ozturk, Mehmet; Mayerle, Roberto (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
Compared to tidal currents, which have been extensively researched in recent years, relatively little attention has been paid to the energy potential of waterways characterised by non-tidal or stratified ocean currents, such as the Bosphorus Strait in Istanbul. Therefore, it is essential to highlight the significance of such domains in the context of marine renewable energy and to provide scientific approaches for assessing their resource potential. This study identifies key considerations for determining suitable Marine Current Turbine (MCT) deployment sites in a sea strait with a stratified flow structure and proposes a site selection methodology accordingly. Floating MCTs were found to be more suitable for capturing the hydrokinetic energy flux of the upper-layer flow toward the southern end of the strait. The spatiotemporal variation in layer thickness was a decisive factor in determining optimal MCT rotor geometry and deployment depth. Turbines notably altered the flow field, particularly during periods of peak current velocities. The MCTs were operational for approximately 80 % of the simulated year and produced an average power of 60 kW. The maximum average power recorded by a single MCT within the turbine array was 83 kW.
Keywords: Bosphorus; Stratification; Ocean renewable energy; Marine current turbine; ISTANBUL BOSPORUS; SEA STRAIT; IMPACTS; GENERATION; Science & Technology - Other Topics; Energy & Fuels